Are Anglican cathedrals more inclusive than parish churches? - Francis, Leslie J. (Theology, 2023)
This article argues that, alongside ethnicity, gender and age, psychological type theory offers a distinctive lens through which to assess the inclusivity agenda of the Anglican Church. On this criterion, empirical data indicate that cathedrals are achieving greater inclusivity than parish churches.